Spatiotemporal Expression of SphK1 and S1PR2 in the Hippocampus of Pilocarpine Rat Model and the Epileptic Foci of Temporal Lobe Epilepsy - Dong, Yuan-Yuan; Xia, Min; Wang, Lin; Cui, Shuai; Li, Qiu-Bo; Zhang, Jun-Chen; Meng, Shu-Shu; Zhang, Yan-Ke; Kong, Qing-Xia (Frontiers in Cell and Developmental Biology, 2020)
Temporal lobe epilepsy (TLE) is a severe chronic neurological disease caused by abnormal discharge of neurons in the brain and seriously affect the long-term life quality of patients. Currently, new insights into the pathogenesis of TLE are urgently needed to provide more personalized and effective therapeutic strategies. Accumulating evidence suggests that sphingosine kinase 1 (SphK1)/sphingosine 1-phosphate receptor 2 (S1PR2) signaling pathway plays a pivotal role in central nervous system diseases. However, the precise altered expression of SphK1 and S1PR2 in TLE is remaining obscure. Here, we have confirmed the expression of SphK1 and S1PR2 in the pilocarpine-induced epileptic rat hippocampus and report for the first time the expression of SphK1 and S1PR2 in the temporal cortex of TLE patients. We found an increased expression of SphK1 in the brain from both epileptic rats and TLE patients. Conversely, S1PR2 expression level was markedly decreased. We further investigated the localization of SphK1 and S1PR2 in epileptic brains. Our study showed that both SphK1 and S1PR2 co-localized with activated astrocytes and neurons. Surprisingly, we observed different subcellular localization of SphK1 and S1PR2 in epileptic brain specimens. Taken together, our study suggests that the alteration of the SphK1/S1PR2 signaling axis is closely associated with the course of TLE and provides a new target for the treatment of TLE.